Neogene diversification in the temperate lichen-forming fungal genus Parmelia (Parmeliaceae, Ascomycota). Issue 2 (4th March 2017) - Molina, M. Carmen; Divakar, Pradeep K.; Goward, Trevor; Millanes, Ana M.; Lumbsch, H. Thorsten; Crespo, Ana
Abstract : The lichen-forming genus Parmelia Acharius occurs worldwide but its centre of distribution is in the northern hemisphere and it is widespread in boreal-temperate Eurasia and North America. Recent molecular work on Parmelia has identified phylogenetic relationships within two major groups of the genus: P. saxatilis s. lat. and P. sulcata s. lat. However, little is known about the diversification and historical biogeography of these groups. Here we have used a dataset of two genetic markers and 64 samples to estimate phylogenetic relationships within Parmelia. The dated phylogeny provides evidence for major diversification during the Neogene and Pleistocene. These diversification events are probably correlated with climatic changes during these periods. Evidence of gene flow within species between populations from North America and Europe has been found in three species: P. sulcata Taylor, P. saxatilis (L.) Acharius and P. barrenoae Divakar, M.C. Molina & A. Crespo. Cryptic species recently segregated on the basis of molecular differences ( P. encryptata A. Crespo, Divakar & M.C. Molina vs. P. sulcata and P. saxatilis vs. P. mayi Divakar, A. Crespo & M.C. Molina) do not share a common ancestor. Moreover, the P. saxatilis complex is remarkably diverse. Two morphotypes of P. saxatilis s. lat. were shown to represent independent monophyletic lineages. Consequently, two species ( P. sulymae Goward, Divakar, & M.C. Molina & A. Crespo and P. imbricaria Goward, Divakar, M.C. Molina & A. Crespo) are newly described here.